Evaluation of Short Term Fever with Flu like Symptoms in a Tertiary Level Hospital in Bangladesh (Medicine Today, 2016)
Short term fever, a major public health concern is commonly caused by influenza virus. This is a crosssectional surveillance study designed to identify common causes of short term fever and diversity of causative different viral strains specially influenza virus, done in medicine and pediatrics department, Comilla Medical College Hospital, Bangladesh from November 2013 to October 2014. Patients having fever with flu like symptoms for less than 7 days was selected. Nasopharyngeal swab was analyzed by RT-PCR for detection of influenza A and B with other respiratory virus. Routine blood test, Malaria detection, blood culture for Salmonella, urine culture was done.Out of 529 patients virus was isolated in 122, of which Influenza, non influenza and mixed viral pathogens was isolated in 65,48 and 9 patients respectively. Salmonella, Malarial parasites and urinary tract infection (UTI) was found in 40, 4 and 8 cases respectively. Sixty five patients was detected influenza A and B (31vs34), with both A & B in one patient. Most of Influenza A and B cases were found in early monsoon. Among Influenza A positive cases, 29 belonged to H3N2 and 2 cases H1N1 (pdm09) subtype. This study revealed influenza A and B, salmonellosis and other non influenza viruses as main etiology of short term fever. RT PCR for virus is an important investigation for viral detection. Blood and urine culture is adjunctive investigation to detect salmonellosis and UTI. No avian and swain flue was detected.Medicine Today 2015 Vol.27(2): 5-8